2014
DOI: 10.1073/pnas.1403565111
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand breaks promote methylation of histone H3 on lysine 9 and transient formation of repressive chromatin

Abstract: Dynamic changes in histone modification are critical for regulating DNA double-strand break (DSB) repair. Activation of the Tip60 acetyltransferase by DSBs requires interaction of Tip60 with histone H3 methylated on lysine 9 (H3K9me3). However, how H3K9 methylation is regulated during DSB repair is not known. Here, we demonstrate that a complex containing kap-1, HP1, and the H3K9 methyltransferase suv39h1 is rapidly loaded onto the chromatin at DSBs. Suv39h1 methylates H3K9, facilitating loading of additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
335
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(383 citation statements)
references
References 48 publications
32
335
3
1
Order By: Relevance
“…Further, we showed H2A.Z retention at DSBs blocked the shift to open chromatin, indicating that the initial exchange of H2A.Z stabilizes chromatin immediately after DNA damage. Other repressive factors, including HP1 and NuRD (10,(40)(41)(42), are also rapidly, but transiently recruited to DSBs. Transient loading of H2A.Z and other repressors may therefore temporarily "heterochromatinize" nucleosomes at breaks, stabilizing the damaged chromatin, and allowing the cell time to process the chromatin for DNA repair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we showed H2A.Z retention at DSBs blocked the shift to open chromatin, indicating that the initial exchange of H2A.Z stabilizes chromatin immediately after DNA damage. Other repressive factors, including HP1 and NuRD (10,(40)(41)(42), are also rapidly, but transiently recruited to DSBs. Transient loading of H2A.Z and other repressors may therefore temporarily "heterochromatinize" nucleosomes at breaks, stabilizing the damaged chromatin, and allowing the cell time to process the chromatin for DNA repair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent these finding apply to human cells is unclear, given the differences in telomere biology between humans and mice (Calado and Dumitriu, 2013). Furthermore, a number of findings demonstrate that induction of a condensed heterochromatic state can even promote DNA repair and/or homologous recombination (Ayrapetov et al, 2014;Geuting et al, 2013). A recent study of DDR signaling in U2OS cells is particularly informative on this issue (Burgess et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, cytological studies revealed that H3K9me-deficient mutants exhibit spontaneous DSBs in heterochromatin, and it was proposed that this damage is due to defective DNA replication (2,29,30). Mice lacking Lysine (K) Methyltransferase 1A (KMT1A) (SUV39H1) and KMT1B (SUV39H2) exhibit genome instability and high rates of lymphoma development (31,32), and both KMT1 enzymes and HP1 proteins have been implicated in DNA repair in animals (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). These and other studies suggest that heterochromatin components have important roles during both DNA replication and DNA repair, but the heterochromatin-dependent mechanisms that maintain genome integrity remain poorly defined.…”
Section: Significancementioning
confidence: 99%